2013
DOI: 10.1159/000354570
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type-I and Pyogenic Granuloma: A Vascular Endothelial Growth Factor-Mediated Association

Abstract: Pyogenic granuloma (PG) is a vascular endothelial growth factor (VEGF)-related neoangiogenic process. Minor trauma, chronic irritation, certain drugs and pregnancy may favor PG. Viral triggers have not been reported up to date. A 52-year-old woman with hairy-cell leukemia presented because of a 3-month history of a giant pseudotumoral lesion on her left cheek. All prior antibacterial, antifungal and anti-inflammatory treatments had failed. Histology revealed PG with sparse and isolated epithelial cell aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
2
9
0
3
Order By: Relevance
“…reported pyogenic granuloma like lesions caused by bacillary angiomatosis (BA). El Haydari et al . reported pyogenic granuloma like lesions after herpes virus infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…reported pyogenic granuloma like lesions caused by bacillary angiomatosis (BA). El Haydari et al . reported pyogenic granuloma like lesions after herpes virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma, chronic irritation, some drugs, and pregnancy can trigger a pyogenic granuloma. [8][9][10] El Hayderi et al 12 reported a pyogenic granuloma after HSV-1 infection. Midilli et al 13 reported a nosocomial outbreak of disseminated orf infection in a burn unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Da das Granuloma pyogenicum in der Regel wiederholt blutet und keine spontane Abheilungstendenz zeigt, ist eine operative Abtragung sinnvoll. Neben Traumen, hormonellen Faktoren und Medikamenten scheint insbesondere – ähnlich der durch Bartonella henselae induzierten bazillären Angiomatose – eine mikrobiologische Kolonisation mit Bakterien oder Viren , welche proangiogene Zytokine wie VEGF produzieren, an der reaktiven Gefäßproliferation von pathogenetischer Relevanz zu sein. Histologisch findet sich ein von einer lateralen epidermalen Collerette eingefasster, lobulär gegliederter, kapillärer Tumor (Abbildung a, b).…”
Section: Tumoren Des Säuglingsaltersunclassified
“…It is believed that trauma and female sex hormones enhance expression of angiogenic factors such as basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF) which will lead to evolution of the pyogenic granuloma [6,7,11,15]. Medications such as isotretinoin, acitretin, cyclosporine, lamivudine, docetaxel, imatinib, and indinavir may also be contributing factors [8,13,[15][16][17][18]. Infections such as caused by herpes simplex type-I and Epstein-Barr virus have also been incriminated [18].…”
Section: Etiology and Pathogenesismentioning
confidence: 99%